2015
DOI: 10.2217/fvl.15.103
|View full text |Cite|
|
Sign up to set email alerts
|

Association Between Serum Aminotransferase enzymes–lipid Profile Ratio and Spontaneous HCV Clearance in Blood Donors

Abstract: Aim: Study the role of the aminotransferase lipid profile ratio in the spontaneous clearance of HCV. Materials & methods: Blood samples from 68 blood donors were classified into three groups: negative for HCV antibodies (control group I), positive anti-HCV with negative HCV-RNA, (group II) and positive anti-HCV with positive HCV-RNA (group III). Results: A significant linear correlation was observed between the HCV-RNA levels and aminotransferase enzymes–lipid profile ratio as indicated by the values of (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…It was reported that the mean HAI and fibrosis scores of the PCR negative women were also significantly lower than those of PCR positive women (p=0.000). 23 Also, the present study showed that CHC patients had significantly lower PLC than SVC subjects. This could be explained by the presence of hypersplenism, decreased platelet production due to decreased hepatic thrombopoietin (TPO) secretion and CHC induced bone marrow suppression.…”
Section: Discussionsupporting
confidence: 63%
“…It was reported that the mean HAI and fibrosis scores of the PCR negative women were also significantly lower than those of PCR positive women (p=0.000). 23 Also, the present study showed that CHC patients had significantly lower PLC than SVC subjects. This could be explained by the presence of hypersplenism, decreased platelet production due to decreased hepatic thrombopoietin (TPO) secretion and CHC induced bone marrow suppression.…”
Section: Discussionsupporting
confidence: 63%